FIRST RUSSIAN TYPE 2 DIABETES MELLITUS SIMULATION MODEL WITH DISCREET EVENTS MODELING. HEALTH-ECONOMIC ANALYSIS - A. S. Kolbin; O. K. Khmelnitskiy; A. A. Kurylev; Yu. E. Balykina; M. A. Proskurin; E. P. Kolpak; M. V. Bure (IRBIS LLC, 2015)
Goal: to develop the model of of type 2 diabetes mellitus outcomes validated in Russian clinical conditions and to perform pharmacoeconomic evaluation of glucose lowering therapies. Materials and methods: Existing type 2 DM models were evaluated. Risk equations for type 2 DM complications were compiled. Demographic, biochemical etc. patient parameters were used as input parameters. Glucose lowering drug's effectiveness were incorporated into the model as its ability to modify input parameters (HbA1c, lipids, etc.). Cost-effectiveness analysis was performed. Results: The developed model allows to assess the risk of type 2 DM complications in 5 years in patient with predefined risk factors. Among comparing strategies of type 2 DM therapies liraglutide (Victoza®) was considered as the cost-effective strategy with ICER/QALY - 470 120.40 RUR, which is 51% of the willingness-to-pay threshold in Russia. With the lowest complication treatment costs inside the total direct costs, liraglutide monotherapy demonstrated the most long-term sustainable glycemic control and HbA1c goal parameters.